AN EXPERIENCE OF IMPLEMENTING LIMS SYSTEM IN THE BIOANALYTICAL LABORATORY (PART 1) - A. A. Krylatova; I. E. Shohin; A. S. Kardashin (Разработка и регистрация лекарственных средств)
Center of Pharmaceutical Analytics purchased and installed LabWare LIMS laboratory information system, LabWare ELN electronic laboratory journals from LabWare company. At the moment, the system is integrating into the work of the laboratory, templates for research work are created and employees are trained. The article opens a series of articles of the integration of the LIMS system into the work of the analytical center. LabWare has received universal recognition, is a leader in the global market of global Laboratory information systems (LIMS) and has a wide range of loyal users.